2015
DOI: 10.1002/ccr3.194
|View full text |Cite
|
Sign up to set email alerts
|

Placenta accreta: adherent placenta due to Asherman syndrome

Abstract: Key Clinical MessageIt is important to be aware of the risk of abnormally invasive placenta in patients with a history of Asherman syndrome and uterine scarring. A prenatal diagnosis by ultrasonography is useful when planning of mode of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…In addition, obstetric complications should be observed, including placentation issues, prematurity and postpartum hysterectomy following treatment for IUAs (47). For example, intrauterine adhesions may lead to placenta accreta and the risk of severe postpartum haemorrhage (48). However, to the best of our knowledge, whether aspirin may decrease the obstetric complications with IUAs following surgery has not yet been described in the literature and requires long-term follow-up observations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obstetric complications should be observed, including placentation issues, prematurity and postpartum hysterectomy following treatment for IUAs (47). For example, intrauterine adhesions may lead to placenta accreta and the risk of severe postpartum haemorrhage (48). However, to the best of our knowledge, whether aspirin may decrease the obstetric complications with IUAs following surgery has not yet been described in the literature and requires long-term follow-up observations.…”
Section: Discussionmentioning
confidence: 99%
“…The current results agreed with researchers who found increases in TNF, IL-1β, and IL-6 in bronchoalveolar lavage fluid in pulmonary fibrosis rat model [ 23 ]. Estrogen can promote the growth of endometriotic lesions by increasing the TNF levels [ 24 ]. BMSCs treatment resulted in the regeneration of the endometrium via modulation of the expression of proinflammatory cytokines TNF and IL-1 in experimental rats [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent case study has reported an abnormally invasive placenta as a result of uterine scarring in a patient with Asherman's syndrome. 18 Therefore, awareness of the possible development of MAP is important in pregnant women with a history of intrauterine procedure without caesarean section scar or placenta praevia.…”
Section: Discussionmentioning
confidence: 99%